Rapid manipulation of extracellular vesicles using dielectrophoretic mechanism - Nur Mas Ayu Jamaludin; Muhammad Khairulanwar Abdul Rahim; Azrul Azlan Hamzah; Nadiah Abu; Muhamad Ramdzan Buyong (Penerbit Universiti Kebangsaan Malaysia, 2020)
Extracellular vesicles (EVs) are small entities that are released by most cell types. EVs are important form of intercellular communication and a rich source of biomarkers for a wide variety of diseases. Many methods for EVs isolation have been utilized, however, most of them have significant drawbacks including lengthy processing time, high cost, shortfalls in selectivity and surface marker dependency. In consideration of these issues, this paper discussed on the dielectrophoresis (DEP) microelectrode method designed to rapidly isolate EVs from its medium. The advantage of this DEP microelectrode is the capability of isolating EVs using a droplet of 1 µL placed onto the microelectrode within 30 s and 20 V peak-to-peak (Vp-p) of alternating current (AC). The method used in the characterization of sample are dynamic light scattering (DLS) and transmission electron microscopy (TEM); both prove the heterogeneity of EVs’ population and the EVs appear to be spherical with size ranging from 40 to 200 nm. The experimental results from this preliminary experiment show that the DEP microelectrode was able to manipulate EVs as evidenced by the negative dielectrophoresis (NDEP) fluorescent images. Further investigation of grid analysis conducted shows the consistency of the theory and the results presented. Corrected Total Cell Fluorescence (CTCF) values from the grid analysis concluded that the EVs were manipulated to the center of region of interest, (ROI). Therefore, this DEP technique suggests a rapid strategy for EVs isolation from its medium in small quantity while maintaining accuracy and cost-effectivity.